2020
DOI: 10.1088/2058-8585/ab7bc3
|View full text |Cite
|
Sign up to set email alerts
|

Flexible substrate with floating island structure for mounting ultra-thin silicon chips

Abstract: A flexible substrate with a novel floating island structure design was developed for mounting ultra-thin silicon chips. The structure reduced the strain propagated from the stretching base to the ultra-thin silicon chips. While conventional structures reduce strain by 64.2%, the floating island structure reduced strain by 90.2%. Furthermore, tests for operational stability and durability were conducted using an ultra-thin operational amplifier (OPAMP) mounted on the flexible substrate with a floating island st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Being flexible makes UTC a great choice when the sample is exposed to bending, folding or twisting. Nonetheless, UTC is susceptible to cracking under tensile stress [29]. As a result, the failure of these samples at 30% strain was attributed to the UTC cracking, which was also verified experimentally (figure 4(b)).…”
Section: Stretchability After Chip Mounting Without Encapsulationsupporting
confidence: 73%
“…Being flexible makes UTC a great choice when the sample is exposed to bending, folding or twisting. Nonetheless, UTC is susceptible to cracking under tensile stress [29]. As a result, the failure of these samples at 30% strain was attributed to the UTC cracking, which was also verified experimentally (figure 4(b)).…”
Section: Stretchability After Chip Mounting Without Encapsulationsupporting
confidence: 73%
“…Additionally, we previously demonstrated that it is possible to reduce the strain transmission using a floating island structure. (23) However, this previous investigation did not consider the sealing of the UTC. As shown in Fig.…”
Section: Introductionmentioning
confidence: 97%
“…There have been several attempts at integrating thinned silicon microprocessor dies on to flexible substrates [59,88]. While this hybrid integration can sometimes meet conformality requirements, cost continues to be a limitation [92] due to the high cost of silicon manufacturing (integration costs increase as well).…”
Section: Introductionmentioning
confidence: 99%